The influence of built environment on travel behavior of the elderly in urban China. (May 2017) - Feng, Jianxi
Highlights: Chinese socio-cultural contexts make the travel patterns of the elderly special. Public transportation accessibility exerts more influences than that of auto on seniors' travel behavior. Vegetable markets are more influential than supermarkets for the elderly. Open spaces/parks are more attractive than gyms for the elderly. Abstract: Along with the aging trend of the world population, the status and determinants of the travel behavior of the elderly have been gaining more attention in planning and research. Most of the existing research has focused on the influence of socio-demographics and built environments, while the impact of socio-cultural backgrounds has attracted less attention. Regarding the influence of built environments, previous studies have mainly focused on general elements such as density, and land use mixture, while specifics about how built environments influence the elderly have largely been ignored. This paper, therefore, attempts to investigate how socio-cultural settings, interacting with built environments, affect the travel behavior of the elderly in urban China. Particularly, we will examine the impacts of a set of built environment attributes on daily activity participation and the travel distance of the elderly in Nanjing. Based on quantitative and qualitative data, we found that special social and cultural contexts make the travel pattern of Chinese elderly and the determinants of that pattern different from those of their western counterparts. Specifically, it was found that public transportation accessibility instead of auto transportation accessibility, vegetable markets instead of supermarkets and convenience stores, open spaces and parks along with chess and card rooms instead of gyms and sports centers are more decisive in affecting the travel behavior of the elderly. These findings offer insights for policy making on distributing appropriate public facilities for the elderly in urban areas, especially in new towns in urban China.